Forest fire propagation simulations for a risk assessment methodology development for a nuclear power plant. (October 2015) - Okano, Yasushi; Yamano, Hidemasa
Highlights: Potential challenges to a nuclear power plant (NPP) by a forest fire are analyzed. Forest fire propagation simulations are performed on a typical NPP site condition in Japan. Intensity and key parameters related to "heat" and "flame" effects are evaluated. The parameters are sensitive to prevailing wind speed and relative humidity. Loss of offsite power of a NPP is recognized as a possible subsequence by a forest fire. Abstract: After the Fukushima Daiichi nuclear power plant [NPP] accident, there has been an increased concern with the safety of NPPs in terms of external hazards, one of which is a forest fire which can create potential challenges to safety functions and the structural integrity of an NPP. As a part of the development of a risk assessment methodology for forest fires as an external hazard, forest fire propagation simulations have been performed by using the FARSITE simulator. These simulations have been used to evaluate two intensity parameters (i.e. fireline intensity and reaction intensity) and three other key parameters (i.e. flame length, rate-of-spread, and forest fire arrival time) which are related to "heat" and "flame" effects on an NPP. Sensitivity analyses for a wide range of weather conditions were performed in order to identify the variable ranges of the intensity and other key parameters. The location studied was selected from among areas with typical topographical and vegetation surrounding NPPs in Japan. The NPP is facing the sea and surrounded by hills, distanced from an urban area, with mostly broad leaf forests, several paddy fields and a few pasture areas. Low-to-high frequency weather conditions have been utilized in this analysis; forest fire propagation simulations were performed "with/without prevailing wind" (i.e. 0–24 m/s wind speed) and "high/low values for ambient temperature and relative humidity" (−4.3 to 37 °C and 5–99%, respectively) according to the recorded data ranges for the typical NPP site. The maximum values of fireline intensity and rate-of-spread are 4.7 × 10 2  kW/m and 2.4 m/min and they depend very much on prevailing wind speed and relative humidity (around 2.3 and 1.8 times respectively) but less on ambient temperature (around 1.1 times). Reaction intensity and flame length change within relatively narrow ranges (around 1.7 and 1.5 times respectively) even for all the variation in weather parameters. The forest fire arrival time at the site is reduced by a factor of 5 with changing prevailing wind speed from the recorded-highest to zero. The arrival time increases some 3.4 times with the highest humidity compared to the recorded-lowest conditions, although it is changed little even by varying ambient temperature. Given that this study shows that the maximum height of a flame on a canopy top is close to the range of power line height, a loss of offsite power is recognized as a possible subsequent event during a forest fire.